Peran Escrow Services sebagai Variabel Pemoderasi di Marketplace - Kusumawati, Ratna Dewi; Achjari, Didi (Jurnal Ekonomi Indonesia, 2019)
Previous studies show that Perceived Effectiveness of Escrow Service (PEES) affects the relationship. In e-commerce, trust can be seen as a trust in the community of sellers and trust in intermediaries. The purpose of this study is to investigate the role of PEES to moderate relationship between trust in intermediaries and repurchase intentions, and between trust in the community of sellers and repurchase intention. This research was administered to 138 respondents through online survey. The findings indicate that PEES moderates not only the relationship of trust in intermediaries and repurchase intentions, but also the relationship between trust in the community of sellers and repurchase intentions. Keywords: trust to community of seller; trust to intermediary; perceived effectiveness of escrow services; repurchase intentions; e-commerce ———————————- Penelitian terdahulu menunjukkan bahwa Perceived Effectiveness of Escrow Service (PEES) mempengaruhi hubungan kepercayaan kepada komunitas penjual dan intensi pembelian kembali. Dalam konteks e-commerce, kepercayaan dapat dipandang sebagai kepercayaan kepada komunitas penjual dan kepercayaan kepada perantara. Tujuan dilakukannya penelitian ini adalah untuk meneliti peran moderasi PEES terhadap hubungan antara kepercayaan kepada perantara dan intensi pembelian kembali, serta kepercayaankepada komunitas penjual dan intensi pembelian kembali. Penelitian ini dilakukan kepada 138 responden melalui survei daring. Temuan dari hasil uji menunjukkan bahwa PEES memoderasi hubungan antara kepercayaan kepada perantara dan intensi pembelian kembali, serta kepercayaan kepada komunitas penjual dan intensi pembelian kembali.